2014
DOI: 10.3889/oamjms.2014.052
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Brain Metastasis of Endometrial Stromal Sarcoma

Abstract: High-grade endometrial stromal sarcoma is a rare uterine malignancy. The cells of these tumors resemble endometrial cells in the proliferation stage, with many small plexiform arterioles. Herein we present a patient with endometrial stromal sarcoma that metastasized to the brain, along with the CT and MRI findings and a discussion of the surgical and histopathological features of the metastatic tumor. Immunohistopathological examination of the metastatic tumor showed a high mitotic rate and strong immunopositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Brain metastases from endometrial stromal sarcoma (ESS) have rarely been reported in the literature. [ 1 ] Here, we described a case of ESS where brain metastases necessitated an emergency craniotomy, and a left atrial thrombus (LAT) (55 × 41 × 26 mm) was accidentally discovered preoperatively.…”
mentioning
confidence: 99%
“…Brain metastases from endometrial stromal sarcoma (ESS) have rarely been reported in the literature. [ 1 ] Here, we described a case of ESS where brain metastases necessitated an emergency craniotomy, and a left atrial thrombus (LAT) (55 × 41 × 26 mm) was accidentally discovered preoperatively.…”
mentioning
confidence: 99%